UPAYA PENINGKATAN KESEJAHTERAAN SOSIAL MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA DI DESA SUNGSANG I KECAMATAN BANYUASIN II KABUPATEN BANYUASIN - Nurwahyuliningsih, Eka; Pusnita, Indah; Fitria, Fitria (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2022)
This research aims to determine efforts to improve community social welfare through tourism village development activities. The locus of the research was carried out in Sungsang I Village, Banyuasin II District, Musi Banyuasin Regency, and the informants in this research were the local community, local government and tourists. This research uses qualitative methods, while data collection techniques use direct observation and non-participant observation, interviews and documentation. This research focuses on four components of tourism, so the results of the research include Attraction that Sungsang I Village has natural beauty and performing arts which become a tourism magnet for tourists to visit the village; Accessibility, for accessibility, Sungsang I Village already has several infrastructure facilities that are quite adequate, although there needs to be additional facilities to support sustainable tourism activities, such as improving the mode of transportation to the tourist village; Amenities, which are related to the supporting facilities of Sungsang I Village as a tourism destination, this component is an important aspect that must be completed by all tourism actors in Sungsang I Village; in the case of Ancillary in Sungsang I Village, the local government and local community work together with groups who care about tourism to support the sustainability of the tourist village, then tourists can find several homestays, prayer rooms, souvenir shops, interesting photo locations, and other culinary places in Sungsang Village I. There are still several obstacles to infrastructure progress in Sungsang Village, such as damaged roads and a limited number of accommodations due to the lack of investors investing in the area. Even though there are still obstacles in its implementation, at least the development of tourist villages can help local communities to be economically empowered by providing entrepreneurship opportunities, improving local community skills, preserving local traditions and culture, and local communities must still maintain the principles of sustainable tourism.